Tutankhamun, the Untold Story - Thomas Hoving 1931-2009 (USA Simon and Schuster, 1978)
Recounts the events and the people involved in the discovery of Tutankhamun's tomb in 1922
Dramatis personae -- The Stage : the Valley of the Kings -- Forty kings and the thieves from Kurna -- First clues of Tutankhamun -- The First years of search -- Deep doubts -- The "Tomb of the golden bird" -- "Wonderful things" -- The Long night -- Revelations -- The Limelight -- "Discovery colossal and need every assistance" -- The Affair of the three princesses -- The Metropolitan Museum makes a coup -- "Tutankhamun Ltd." -- A "Renegade" speaks out -- "Strong bull, beautiful of birth -- Carnarvon returns to the tomb -- The Sealed doorway -- The Queen's visit -- Closing down the tomb -- Sudden tragedy -- The Curse -- The Season ends -- Collision course -- The Bastion of bureaucracy -- Dismantling the shrines -- The "Public domain" -- Strike! -- "Bandits!" -- A "Malignant influence" -- " Much Kalaam" -- Carter in America -- Surrender -- The Secret division.
Includes index
Keywords: Excavations (Archaeology) -- Egypt; Archaeology; Ancient Egypt; General